A Review of Educational, Psycho-Social, and Attitudinal Challenges in Addressing the Needs of Students with Disabilities in Inclusive Education - Ibsa Negash; Yadavalli, Pavan Kumar (International Journal of Psychosocial Rehabilitation, 2020)
This review addressed challenges to addressing the needs of students with disabilities in inclusive Ethiopia related to educational, psychosocial, and attitudinal challenges. In order to conduct the review, the reviewer downloaded relevant articles on the topic, read them thoroughly, and selected 10 relevant articles for a review. The review employed a narrative review, in which major findings of the articles were narrated according to their similarities under three themes (i.e., education, psychosocial, and attitude). First, the analysis of studies demonstrated that the education of students in inclusive settings is far from practical and not as speculated in different policy frameworks and strategies. It is hindered by barriers related to a lack of educational material resources, a lack of skilled manpower on the issue of educating students with disabilities, and an inaccessible physical environment for SWDs to enroll in school. Second, psycho-social problems related to students with disabilities are observed due to their disabilities; there is discrimination, prejudice, and the stereotype that students with disabilities do not have access to equal opportunities, as well as an unpleasant relationship among the school community and students. This makes students with disabilities poor at social interaction, leads them to worry about their disabilities, and leads them to live separately. Third, the attitude of society’s way of thinking and perception of persons with disabilities as weak, unable, hopeless, dependent, and unable to learn prevailed, and they were considered the subject of charity from the side of teachers, the school community, and students without disabilities. These challenges intensify the impact of disability on individuals and social aspects in general. Based on these facts, the necessity of removing barriers to learning and practice to raise awareness of disability through ongoing training of societies, an accessible environment, equipping schools, and working on raising awareness helps overcome the challenges